2022
DOI: 10.3389/fphys.2022.800218
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid System in Rainbow Trout Telencephalon Is Probably Involved in the Hedonic Regulation of Food Intake

Abstract: We hypothesize that opioids are involved in the regulation of food intake in fish through homeostatic and hedonic mechanisms. Therefore, we evaluated in rainbow trout (Oncorhynchus mykiss) hypothalamus and telencephalon changes in precursors, endogenous ligands and receptors of the opioid system under different situations aimed to induce changes in the homeostatic (through fasted/fed/refed fish) and hedonic (through feeding fish a control or a palatable high-fat diet) regulation of food intake. No major change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
1
0
2
Order By: Relevance
“…In contrast, in previous study of the same RT, we observed a higher serotonin level in the telencephalon, which is the major centre for decision making that receives serotonin neurons inputs in fish, during a fasting period (24) . The telencephalon can be responsible for this hedonic sensation in RT (58) . In the same way, in this area, the precursor of dopamine (L-DOPA), a neurotransmitter that is a marker of the stress response, motivation and ill-being when high in a chronic situation or due to long-term effects of feeding (24) , was higher in RT fed the V diet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in previous study of the same RT, we observed a higher serotonin level in the telencephalon, which is the major centre for decision making that receives serotonin neurons inputs in fish, during a fasting period (24) . The telencephalon can be responsible for this hedonic sensation in RT (58) . In the same way, in this area, the precursor of dopamine (L-DOPA), a neurotransmitter that is a marker of the stress response, motivation and ill-being when high in a chronic situation or due to long-term effects of feeding (24) , was higher in RT fed the V diet.…”
Section: Discussionmentioning
confidence: 99%
“…Хемореактомный анализ указал на умеренные антиопиоидные эффекты фонтурацетама по отношению к опиоидным рецепторам типов мю / каппа / дельта (IC50 = 642 нМ, остальные молекулы 1030-9438 нМ). Метаанализ доклинических исследований подтвердил анорексигенные эффекты опиоидных антагонистов [32]. Антагонисты опиатов можно использовать при лечении компульсивного переедания [33].…”
Section: хемореактомное исследование эффектов фонтурацетама: молекуля...unclassified
“…Фармакологические исследования опиатов и их антагонистов показали, что ингибирование опиатных рецепторов может быть использовано для лечения булимии [38]. Настоящее исследование указало на антиопиоидные эффекты 4-фенилпирацетама для рецепторов подтипов мю/каппа/дельта (IC50=642 нМ, другие рацетамы 1030-9438 нМ).…”
Section: ингибирование опиоидных рецепторовunclassified